The NASSAU (New ASSessment of cerebral Arteriovenous Malformations yet Unruptured) Analysis: Are the Results From The ARUBA Trial Also Applicable to Unruptured Arteriovenous Malformations Deemed Suitable for Gamma Knife Surgery?. Issue 1 (July 2019) - Karlsson, Bengt; Jokura, Hidefumi; Yang, Huai‐Che; Yamamoto, Masaaki; Martinez, Roberto; Kawagishi, Jun; Guo, Wan‐Yuo; Beute, Guus; Pan, David H C; Aiyama, Hitoshi; Chung, Wen‐Yuh; Söderman, Michael; et al.
Abstract : BACKGROUND: : The optimal management of unruptured brain arteriovenous malformations (AVMs) is controversial after the ARUBA trial. OBJECTIVE: : To confirm or repudiate the ARUBA conclusion that "medical management only is superior to medical management with interventional therapy for unruptured brain arteriovenous malformations." METHODS: : Data were collected from 1351 patients treated with Gamma Knife Surgery (GKS; Elekta AB, Stockholm, Sweden) for unruptured and untreated AVMs The follow‐up was 8817 yr (median 5.0 and mean 6.5). The results of the analyses were compared to that found in patients randomized to medical management only in the ARUBA trial and extrapolated to a 10‐yr time period. Our data were also compared to the natural course in a virtual AVM population for a 25‐yr time period. RESULTS: : The incidence of stroke was similar among ARUBA and our patients for the first 5 yr. Thereafter, the longer the follow‐up, the relatively better outcome following treatment. Both the mortality rate and the incidence of permanent deficits in patients with small AVMs were the same as in untreated patients for the first 2 to 3 yr after GKS, after which GKS patients did better. Patients with large AVMs had a higher incidence of neurological deficits in the first 3 yr following GKS. The difference decreased thereafter, but the time until break even depended on the analysis method used and the assumed risk for hemorrhage in patent AVMs. CONCLUSION: : The ARUBA trial conclusion that medical management is superior to medical management with interventional therapy for all unruptured AVMs could be repudiated.